Muscle strength and muscle contractile properties in response to 16 weeks of high and moderate intensity linear versus daily non-linear resistance training - Holzinger, S.; Rasche, C.; Soleimani, M.; Ullrich, B.; Pfeiffer, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Classic linear (CLP) and non-linear (NLP) strength training periodization result both in significant strength gains. Some studies indicate daily nonlinear periodization (dNLP) possibly more effective for strength gains (Kok et al., 2009). Others show motor performance and power increases are not significantly different between dNLP and CLP (Hartmann et al., 2009). Studies lacked to clarify the controversy of preference of CLP or NLP strength training regimes. There is rare information about adaptions in muscle contractile properties in response to CLP and dNLP isometric strength training exercising a specific muscle group with similar overall training volume and intensities. Methods: Thirteen recreational active students (25 years, 10 women/ 3 men) participate on a 16 wks supervised isometric strength training program for the knee extensors: 7 wk training phase 1 (TP1), 2 wk brake, 7 wk training phase 2 (TP2). Subjects exercised one leg using CLP and the other leg using dNLP. Exercise intensities varied among 60% to 80% of MVC, the overall intensity zones and training volume were similar among both legs. Isometric knee extension MVC and mechanical muscle response by tensiomyography (TMG) (Šimunic B., 2012). were measured in both legs (m.vastus lateralis) at the beginning (T1/ T3) and end (T2/ T4) of each TP. ANOVA with repeated measures was used to analyze possible time and time * leg (periodization) effects. Results: MVC increased significant in both legs among all four testing occasions. TMG showed a significant increase from T1 to T2 for maximal displacement (Dm) and sustain time (ts). Delay time (Td), contraction time (tc) and relaxation time (tr) indicated no significant changes over time. No significant method relating effects could be observed, except Tr with a significant increase for CLP. Discussion: Results indicated no method related differences of CLP or dNLP on strength. Muscle contractile properties Dm and ts increased from T1 to T2 and decreased from T2 to T3 as a possible result of reduced muscle stiffness after 2 wks brake. The significant increase of Tr for CLP might be a marker for higher muscle stiffness and less muscle flexibility compared to dNLP. Stronger contrasts in terms of undulating periodization might be a future approach.